EMOTIONAL INTELLIGENCE AND TEACHING BEHAVIOUR:ROLE OF EMOTIONAL INTELLIGENCE IN THE SOCIAL-EMOTIONAL CLIMATE OF THE CLASSES OF THE PRIMARY SCHOOL TEACHERS - Tiwari, Gaurang; Pandey, Asha (THE PRIMARY TEACHER, 2011)
The teaching-learning phenomenon occurs in the context of a social situation and hence what superficially appears to be a cognitive enterprise acquires a dimension of human relations in its operational stage. The social-emotional climate in a classroom mainly depends upon the teacher’s behaviour. It is the teacher who steers and guides the proceedings. The classroom climate is thus conditioned by the type of behaviour is exhibited by the teacher in the classroom. Personal and social competencies associated with emotional intelligence of teacher are found to shape the inter-personal relationship, which in turn, shape the teaching behaviour and ultimately social-emotional climate. For finding out the probable association between the emotional intelligence and teaching behaviour, sampled teachers were observed using Flander’s Interaction Analysis Categories (FIACs) and on the basis of the performance on the emotional intelligence test. It was observed that level of emotional intelligence tended to decide the learning environment and socio-emotional climate of a classroom